Curves and Surfaces for Computer Graphics - Salomon, David (Springer New York : Imprint: Springer, 2006)
Computer graphics is important in many areas including engineering design, architecture, education, and computer art and animation. This book examines a wide array of current methods used in creating real-looking objects in the computer, one of the main aims of computer graphics. Key features: - Good foundational mathematical introduction to curves and surfaces; no advanced math required - Topics organized by different interpolation/approximation techniques, each technique providing useful information about curves and surfaces - Exposition motivated by numerous examples and exercises sprinkled throughout, aiding the reader - Includes a gallery of color images, Mathematica code listings, and sections on curves and surfaces by refinement and on sweep surfaces - Web site maintained and updated by the author, providing readers with errata and auxiliary material This engaging text is geared to a broad and general readership of computer science/architecture engineers using computer graphics to design objects, programmers for computer gamemakers, applied mathematicians, and students majoring in computer graphics and its applications. It may be used in a classroom setting or as a general reference.